Analyze of the Effect of Workplace Spirituality on Auditor Dysfunctional Behavior and its Implication to Audit Quality - Bawono Yudyanto Arief Kusumo; Poppy Sofia Koeswoyo; Sofik Handoyo (Journal of Accounting Auditing and Business, 2018)
This study aims to analyze the effect of workplace spirituality on auditor dysfunctional behavior and its implication to audit quality at The Audit Board of The Republic of Indonesia. The research approach used is quantitative and casual design. The number of research samples was 92 auditors taken through proportionate sampling. The data analysis used descriptive and inferential statistical analysis by employing path analysis. The results show that there is a significant negative effect of workplace spirituality on dysfunctional auditor behavior, there is a significant positive effect of workplace spirituality on audit quality, and there is a significant negative effect of dysfunctional auditor behavior on audit quality. The conclusions of the study state that there is a significant effect of workplace spirituality on dysfunctional auditor behavior. Implication to audit quality is that the audit quality can be improved through workplace spirituality and dysfunctional auditor behavior